(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Glaucoma and chronic kidney disease (CKD) are major global health concerns with shared pathophysiological mechanisms including oxidative stress, inflammation, and microvascular damage. Despite growing evidence of their bidirectional relationship, limited research exists on their association in developing countries like Bangladesh. This study aimed to assess the association between chronic kidney disease and glaucoma risk among patients in Bangladesh. Methods: A case-control study was conducted at National Institute of Ophthalmology and Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2023 to June 2024. The study included 115 physician-diagnosed glaucoma cases and 115 age- and sex-matched controls without glaucoma. Data were collected through structured interviews and medical record reviews. Multivariable logistic regression was performed to determine adjusted odds ratios (AOR) while controlling for potential confounders. Results: CKD prevalence was significantly higher among cases (53.0%) compared to controls (13.0%, p<0.001). After adjusting for confounders, CKD patients demonstrated 5.31 times higher odds of developing glaucoma (AOR=5.31, 95% CI: 1.84-15.30, p=0.002). Other significant independent predictors included low monthly family income (AOR=5.88, 95% CI: 2.38-14.49), migraine (AOR=4.10, 95% CI: 1.31-12.85, p=0.016), myopia (AOR=7.73, 95% CI: 1.71-34.94, p=0.008), and history of ocular laser surgery (AOR=4.74, 95% CI: 1.60-14.02, p=0.005). Conclusion: This study provides the first comprehensive evidence of a significant association between CKD and glaucoma risk in Bangladesh. CKD patients should receive routine glaucoma screening, and comprehensive prevention strategies targeting both conditions are needed. JOPSOM 2024; 43(2): 1-9